2005
DOI: 10.1590/s0074-02762005000300021
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subset analyses in healthy adults vaccinated with yellow fever 17DD virus

Abstract: In this study the kinetics of humoral and cellular immune responses in first-time vaccinees and re-vaccinees with the yellow fever 17DD vaccine virus was analyzed. Flow cytometric analyses were used to determine percentual values of T and B cells in parallel to the yellow fever neutralizing antibody production. All lymphocyte subsets analyzed were augmented around the 30th post vaccination day, both for first-time vaccinees and re-vaccinees. CD3 + T cells increased from 30.8% (SE ± 4%) to 61.15% (SE ± 4.2%), C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…ϩ -, and CD8 ϩ -based antiviral immune response (6,9,10,12,16,(30)(31)(32)(33)(34). Although some of these studies used either peptide pools or tetramer-based approaches to address the response to a limited number of viral epitopes (6,9,33), or calculated the percentage of different immune cellular compartments that represented clones induced by vaccination with YFV (reviewed in reference 16), the clonal breadth and complexity of the response to a viral infection has been beyond the reach of available methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ϩ -, and CD8 ϩ -based antiviral immune response (6,9,10,12,16,(30)(31)(32)(33)(34). Although some of these studies used either peptide pools or tetramer-based approaches to address the response to a limited number of viral epitopes (6,9,33), or calculated the percentage of different immune cellular compartments that represented clones induced by vaccination with YFV (reviewed in reference 16), the clonal breadth and complexity of the response to a viral infection has been beyond the reach of available methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although helper T cells are clearly required for the production of YFV-specific Abs (including nAbs), different studies have reported variable levels of induction of CD4 ϩ T cells upon vaccination with YFV (30,31). Some analyses have revealed that cytokineproducing YFV-specific CD4 ϩ T cells can be detected as early as day 2 postvaccination and that they return to baseline by day 28, suggesting that the kinetics of CD4 ϩ T cells precede those of CD8 ϩ T cells (12,32).…”
mentioning
confidence: 99%
“…Studies have suggested that the ability of YF-17D to infect dendritic cells and activate multiple Toll-like receptors may be essential for generating this potent immune response (8,(12)(13)(14). The YF-17D vaccine provides a model to study the immune response to vaccination in human populations, including both cellular and humoral responses, and to dissect the mechanisms of effective vaccine responses (10,(15)(16)(17)(18). Defining vaccine efficacy in African populations is of paramount importance, as these populations are targeted by most of the currently tested vaccines for HIV, tuberculosis, malaria, and dengue virus (DENV) (19).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the YFV 17D vaccine is an excellent and important model for studying human antiviral immunity. Multiple studies have investigated the attributes and dynamics of CD4 ϩ and CD8 ϩ T cell responses following YF vaccination (8)(9)(10)(11)(12). By using a variety of readouts, these studies demonstrated that YFVspecific CD8 ϩ T cell responses are polyfunctional, exhibit distinct surface phenotypic markers, and peak approximately 2 to 4 weeks after vaccination.…”
mentioning
confidence: 99%